Chest x-ray Findings in the Diagnosis and Evaluation of Covid-19 Patients – A Systematic Review - Sadaf Abdul Qadir, Syed Muhammad Yousaf Farooq, Muhammad Yousaf, Syed Amir Gilani, Madiha Mumtaz, Ahmed Ishfaq (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the main radiological feature of chest radiography for diagnosis and evaluation of COVID-19 patients. Methodology: A literature search was performed with the use of search engines. The following search engines provided us articles for this systematic review from until 27 February 2021: PubMed, NCBI, Medline, Medscape, and Google Scholar. We included only those articles in which CXR was performed on infected patients for the detection and evaluation of COVID-19. Results: out of eighty (80) articles, only twelve (12) were included in this review to assess the main radiological feature of chest radiography of COVID-19 patients. Patients who went for chest x-ray have shown following radiographic features with pooled percentages as mentioned GGO 32.38%, consolidation 35.15%, vascular congestion sign 7.92%, nodules 33.57% whereas pleural effusion accounts 19.36%, pneumothorax 18.55%, and lymphadenopathy was noted on 1.96%. Pooled Percentages of radiographic features of COVID-19 patients in right lung, left lung or both affected lungs were 21.32%, 5.77% and 47.78% respectively. This calculation is showing B/L lung involvement is more dominant as compare to right and left lung independently. Conclusion: Chest radiograph can be helpful modality in the diagnosis, evaluation and follow-up of SARS- CoV 2 pneumonia patients. Consolidation, GGO with peripheral distribution of lesion and bilateral pneumonia are most common findings of COVID-19 on chest X-ray. Chest x-ray are the baseline/first line approach for COVID-19 as it is easily available. Moreover, in late stages multiple radiological findings are quite helpful.